Communicating Resilience: Indigenous Knowledge and Community-Based Disaster Self-Mitigation in Rural Indonesia - Nikmah Suryandari; Qolbi Nur Hidayanto; Farida Nurul Rahmawati; Netty Dyah Kurniasari; Juariyah Juariyah (Jogjakarta Communication Conference (JCC), 2026)
Indonesia is a country with a high level of disaster vulnerability, including Sumenep Regency in Madura, which routinely experiences floods, droughts, and tornadoes. The people of Sumenep have developed self-mitigation practices based on local knowledge (indigenous knowledge) despite limited disaster literacy and insufficient formal socialization from government institutions. This study aims to analyse how the ethnographic process of communication shapes and reproduces self-mitigation practices as a community resilience strategy. The research uses a qualitative approach with the ethnographic design of communication in the constructivism paradigm. The informants were purposefully chosen, and they were from BPBD, religious leaders, and people who lived in three villages that are likely to have disasters: Kebunagung, Pasongsongan, and Kertasada. We gathered data through passive participant observation, in-depth interviews, and documentation. Then, we analysed the data in relation to the components of communication situations, communicative events, and communicative actions. The results show that practices such as village rokad during floods, istisqa' prayers during droughts, and symbolic rituals of